Pengaruh Pendapatan Nelayan Terhadap Daya Beli Masyarakat Pesisir di Desa Kayubulan Kecamatan Batudaa Pantai - Olivia S Akili; Meyko Panigoro; Frahmawati Bumulo; Maya Novrita Dama (Yayasan Pendidikan Sudirman Mandiri, 2025)
This study aims to determine whether fishermen's income has an influence on the purchasing power of coastal communities in Kayubulan Village, Batudaa Pantai Subdistrict. This study employs a descriptive quantitative approach with a sample size of 37 households. The instrument used was a questionnaire, and the data were analyzed using simple linear regression analysis. The results of the data analysis indicate that fishermen's income has a significant influence on the purchasing power of the community. The contribution of fishermen's income to purchasing power is 33.3%, while the remaining 66.7% is influenced by other variables not examined in this study,